Prevalence and Characteristic of Human Immunodeficiency Virus (HIV) Patients in the Working Area of Mokoau Community Health Center, Kendari City, Southeast Sulawesi, for the Period 2021-2024 - Risnah Wati; Sarah Soraya Sirajuddin; Tsalsa Anto Ifdanunnisa; Watu Muntu (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Human Immunodeficiency Virus (HIV) remains a global health issue. Southeast Sulawesi, particularly Kendari City, has experienced an increase in HIV cases in recent years. Understanding the prevalence and characteristics of patients is crucial for planning effective health interventions. Objective: To determine the prevalence and characteristics of HIV patients based on year, age, gender, and occupation in the working area of the Mokoau Community Health Center, Kendari City, for the period 2021–2024. Method: This study used a descriptive approach utilizing secondary data from HIV program reports at the Mokoau Community Health Center. The research subjects included all HIV patients recorded between 2021 and 2024, with a total of 56 cases. The sampling technique used was total sampling. Descriptive analysis was performed on variables such as year of occurrence, age, gender, and occupation. Results: The highest number of HIV cases was recorded in 2023 (58.9%), with the dominant age groups being 20–24 years (46.4%) and 25–49 years (14.3%). The majority of patients were male (80.4%). Based on occupation, 39.3% of cases came from groups with unknown employment status, followed by employees and students, each accounting for 26.8%. Conclusion: HIV infection in the Mokoau Community Health Center working area is dominated by men of productive age, with an upward trend in cases in the middle of the study period. These findings confirm the need for prevention interventions targeting young people and adults of productive age, increased access to HIV testing, and outreach to key populations based on local characteristics. Keywords: HIV; prevalence; patient characteristics; age; gender; occupation; Kendari City